Hukum Islam terhadap Transaksi Digital: Studi tentang Jual Beli Online dalam Perspektif Fiqh Muamalah - Ridwan, M Sulaiman; Winario, Mohd; Kamalin, Muhammad (Journal of Legal Sustainability, 2025)
The rapid development of information technology has driven a transformation in buying and selling practices, particularly through digital platforms or online transactions. This study aims to analyze the legal aspects of online transactions from the perspective of fiqh muamalah and to identify the valid conditions for digital transactions according to Islamic principles. The study also examines the compatibility of online buying and selling practices with the core principles of muamalah, such as honesty, clarity of contract, and the absence of gharar (uncertainty) and maysir (speculation). The research method employed is a qualitative-descriptive approach using library research techniques, analyzing classical and contemporary fiqh literature, scholars' fatwas, and regulations related to digital transactions. The data is analyzed normatively through the approach of usul fiqh to assess the legality of digital transactions from an Islamic legal perspective. The findings indicate that, in general, online buying and selling is permissible in Islam as long as it fulfills the essential elements and conditions of a contract, namely the presence of clearly identified seller and buyer, lawful and well-defined objects of transaction, and a valid offer and acceptance (ijab and qabul), even in digital form. However, online transactions are also vulnerable to violations of muamalah ethics, such as fraud, gharar, and delivery delays, thus requiring supervision and a better understanding of Islamic commercial law by both business actors and Muslim consumers. Therefore, education in contemporary fiqh muamalah is crucial to support digital transactions based on sharia principles.